French and Genevan views of Scotland in 1821: Charles Nodier's Promenade de Dieppe aux montagnes d'Écosse and Louis-Albert Necker's Voyage en Écosse et aux Iles Hébrides. Issue 2 (3rd April 2019) - Hollier, John; Hollier, Anita
ABSTRACT: Two books about Scotland, published in French in 1821, offer an interesting contrast, both in the aims of the authors and the style of the accounts they produced. They reveal unexpected similarities too: Louis-Albert Necker's long and detailed account of Scotland, Voyage en Écosse et aux Iles Hébrides, seems typical of the purposive journey of an eighteenth-century naturalist, yet contains historical elements and scenic descriptions more associated with the Romantic Movement; while the avowedly Romantic Charles Nodier includes in his Promenade de Dieppe aux montagnes d'Écosse some very precise natural history along with his impressions of the country. Both authors were marked by their experience of Scotland to a larger extent than they might have foreseen: one spent the rest of his life as a self-proclaimed expert on Scotland after a visit of a few weeks, while the other passed the last twenty years of his life on the Isle of Skye.